KEANEKARAGAMAN MANGROVE DAN KELIMPAHAN MAKROZOOBENTHOS DI DESA BAGAN ASAHAN KECAMATAN TANJUNG BALAI KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Indah L. M Tambunan; Yunasfi Djayus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Bagan Asahan village is one which is in Asahan Regency, which has the great potential of mangrove ecosystemnand diverse biota that live in it. Macrozoobrnthos is one which is potensial mangrove fishery that have economy value. This study aims to know mangrove diversity and macrozoobenthos abudance. The study held in March until April 2017. The study was conducted using purposive sampling method. Plot size was determined using classification category of seedling (2x2 m2), stake (5x5 m2) and tree (10x10 m2) The highest mangrove diversity for the three categories is located on station I with values of 1.94, 1.83 and 1.62. The highest macrozoobenthos abundance is on station II (18.5 ind/m2) and the lowest is at station III (11,66 ind/m2) meanwhile the macrozoobenthos abundance on station I is 15,41 ind/m2.Keywords : Abundance , Diversity, Makrozoobenthos, Mangrove, Tanjung Balai.